The Institutional Basis of Higher Education Research
VIII, 270 p.
Keywords: In the US, the university administration runs its own office of “insti- tional research” in order to base its decisions on systematic information. Furthermore, higher education research can rely on a relatively stable academic basis if study programmes on higher education exist. Again, this is most frequently the case in the United States. Finally, governments and other macro-societal actors sometimes have their own offices or institutes of policy research and prepare the policies of the actors they report to. In addition, research on higher education can be institutionalized in a - riety of ways. Often, research institutes on higher education are quite visible. They were established as specialized research units within or outside insti- tions of higher education; but no common institutional basis can be observed for this type of institution across the countries. Third, the major themes of research on higher education also differ - tween countries. It has frequently been said that in European countries it was more prone to analyse macro-societal issues of higher education, whereas in the US it tended to study the inner life of higher education institutions, s- dents, and the teaching and learning processes.